Perubahan Skema Insentif pada PT Grab dan Gojek: Dampak terhadap Kepuasan Drive - Dina Sarah Syahreza; Hilma Harmen; Fahmi Aditiya; Khairur Rahmah Azjahra; Najha Nawanda Zhufriy; Patricia Wanda Sianturi; Siti Fauziah (Masyarakat Ekonomi Syariah Bogor, 2024)
Incentive changes can have a negative impact on driver satisfaction, leading to feelings of unfair compensation and income uncertainty. These negative consequences can result in a decline in service quality and increased driver turnover. While incentive changes tend to have negative effects, there are also some positive impacts, such as increased earnings for drivers in high-demand areas. Driver satisfaction is crucial for improving driver availability, service quality, platform reputation, and profitability. Therefore, companies need to reconsider their incentive schemes and make appropriate adjustments to improve driver satisfaction. Efforts to enhance driver satisfaction include implementing fair and transparent policies, increasing market demand, educating passengers, developing platform technology, and enhancing driver support. This study employs qualitative methods and secondary data to support the research findings, ensuring the effectiveness and accuracy of the data used.